Integration of Pulsed-Laser ESPI with Spatial Domain Modal Analysis - H. Van der Auweraer; H. Steinbichler; C. Haberstok; R. Freymann; D. Storer (Shock and Vibration)
The present paper discusses the various critical elements of a modal testing system based on pulsed-laser holographic ESPI measurements. Such system allows making very high spatial resolution measurements on panel-like structures at frequencies that are of relevance for the vibro-acoustic behavior.